Access and Control of Resources by Rural Women in North Shewa Zone, Amhara Region, Ethiopia - Tigabie, Abiro; Teferra, Beneberu; Abe, Amsalu (Research on World Agricultural Economy, 2022)
Gender is one of the crosscutting and the prime importance of any development plan and intervention. Rural women play vital roles in agricultural activities to reduce poverty and food insecurity. This study focuses on gender equality in the access and control of agricultural and rural household resources by rural women. The study was conducted in Bassonawerana, Kewot, and Moretinajiru districts of Northern Shewa Zone Amhara region Ethiopia. Data were collected using individual interviews, key informant interviews, and focus group discussions. A total of 252 respondents were selected using purposive sampling, categorical, and then simple random sample selection techniques. Descriptive statistics and Harvard analysis techniques were used to assess the access, control, and utilization of agricultural and household resources in rural areas. Most of the respondents were married. 95% of the study households depend on agricultural activities of crop and livestock farming. The average family size was 5 in which 3 of them were involved in agricultural activities. The average level of education for the households was 2.5 years. Women were involved in on-farm and off-farm income-generating activities but most women had limited access to extension services and agricultural-related training. The benefits of different resources were shared by all family members equally except institutional resources. Poultry was predominantly owned by women while other livestock resources and land resources were owned by both men’s and women’s family members. Provision of women-targeted training and agricultural extension services focused on how to access and control institutional and household resources are vital to enhance their access to institutional resources and improve the production and productivity of women in the rural household and the entire community for livelihood and food security improvements. ER